Malay annals - Brown, C.C. Charles Cuthbert; Leyden, John; Hooker, Virginia Matheson; Hooker, M.B; Cheah, Boon Kheng; Abdul Rahman Ismail (MBRAS reprint, 2009)
Vol.1 : The late C.C. Brown's translation of Raffles MS18 Sejarah Melayu was first published in the Journal of the Malaysian Branch of the Royal Asiatic Society, vol, 25, part 2 and 3 in 1952. Up to now, it has never been published, and is now extremely difficult to obtain. Although scholarly criticism has been levelled at certain aspects of the translation, the view remains that on balance this is still the best translation available in English.